Rentabilidade no setor bancário: Uma análise comparativa entre Bancos Brasileiros e Norte-Americanos - Matias, Alberto Borges; De Miranda Quaglio, Gislaine [UNESP]; De Lima, João Paulo Resende; Sehn, João Gabriel Gomes (Georgetown University Latin America Leadership Program, 2014)
This is a descriptive study that aims to observe the profitability's behavior of Brazilian and North-American banks, considering a period major transformation for the sector. The sample consists of the largest banks selected according to the criterion total assets banks. To analyze variables indices of financial analysis were employed, as well as for comparative purposes were calculated the same indexes for the Brazilian and U.S. banking sector. The study period covers the years 2002 to 2013. Results show that Brazilian banks have higher profitability indicators to American banks, however, has lower margins than these.
Profitability in the banking sector: A comparative analysys between Brazilian and North American Banks
Keywords: Brazilian Banks; North-American Banks; Profitability